Perspectives of Veterans Affairs mental health providers on working with older adults with dementia and their caregivers. Issue 1 (2nd January 2021) - Wyman, Mary F.; Voils, Corrine I.; Trivedi, Ranak; Boyle, Lisa; Goldman, Daniel; Umucu, Emre; Zuelsdorff, Megan; Johnson, Adrienne L.; Gleason, Carey E.
ABSTRACT: Continuing education directed at building providers' skills and knowledge in geriatrics represents a practical approach to addressing the geriatric mental health (MH) care workforce shortage. To inform the development of professional training curricula, we surveyed MH providers (N = 65) at a Veterans Affairs medical center on working with older persons with dementia (PwD) and informal caregivers. Providers rated service provision to PwD and caregivers as highly important but endorsed modest self-efficacy. Half of respondents were minimally confident in managing risk of harm to self or others in a PwD. Respondents believed PwD can benefit from MH treatments, yet identified several barriers to providing care, including inadequate time and staffing resources. Interest in geriatric training topics was high. Findings demonstrate that MH providers at this site value care provision to PwD and caregivers, and desire additional training to serve this population. System-level barriers to MH care for PwD should also be identified and addressed.